1985
DOI: 10.1080/0028825x.1985.10434240
|View full text |Cite
|
Sign up to set email alerts
|

Plant biogeography and the late Cenozoic history of New Zealand

Abstract: Patterns of regional endemism. vicariance. and disjunction in New Zealand higher plants are reviewed. These are discussed in relation to the post-Oligocene history of the geology. climate .. and vegetation. Previous explanations for su~h distrIbution patterns have centred on the disruptive effects of ice and severe climates during the Last Glaciation. and subsequent migration of plants from glacial refugia during the postglacial. It is conel uded that these explanations are largely Inadequate. It is suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
321
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(337 citation statements)
references
References 39 publications
15
321
1
Order By: Relevance
“…Present evidence suggests that shrublands and grasslands were widespread during the Otiran on the West Coast of South Island, south of Westport (McGlone 1985). No information is available for northwest Nelson although Macphail (1983) has shown that the early Holocene vegetation was dominated by Nothofagus menziesii and Cyathea smithii later replaced by N.fusca group.…”
Section: Glacial Chronology Of Northwest Nelson and Its Vegetation Himentioning
confidence: 96%
See 2 more Smart Citations
“…Present evidence suggests that shrublands and grasslands were widespread during the Otiran on the West Coast of South Island, south of Westport (McGlone 1985). No information is available for northwest Nelson although Macphail (1983) has shown that the early Holocene vegetation was dominated by Nothofagus menziesii and Cyathea smithii later replaced by N.fusca group.…”
Section: Glacial Chronology Of Northwest Nelson and Its Vegetation Himentioning
confidence: 96%
“…However, none of these studies was for western areas of northwest Nelson, and, because they were mostly concerned with glacial chronology, were done near former glaciers where grassland/ shrubland would have been much more likely to occur. As indicated by McGlone (1985), in these former studies,pollen samples were taken from sites of rapid sediment accumulation that were likely to have been sparsely vegetated.…”
Section: Glacial Chronology Of Northwest Nelson and Its Vegetation Himentioning
confidence: 99%
See 1 more Smart Citation
“…Most areas which lackNothofagusare characterised by maritime superhumid climates with comparatively small annu~temperature ranges and probably only rarely expenence drought. Even authors supporting the glacial refugia hypothesis realised the competitive advantages of podocarp-broadleaved forest species over Nothofagus under such climatic conditions (Wardle 1963;Burrows 1965), but assumed that this would only retard the process of re-immigration, McGlone (1985) proposed an alternative "tectonic" hypothesis which implies that the major floristic disjunction between the north-western and south-western South Island is the result of rapid large-scale environmental change since the Late Miocene. He assumes that the displacement of Nelson and Fiordland along the Alpine Fault in connection with the rapid rise of the Southern Alps created an extensive novel habitat in central Westland which is more suitable for the resident podocarp-broadleaved forest and related montane and subalpine vegetation types than to the otherwise widespread Nothofagus forests, which are excluded by biological competition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors have expressed doubts about the concept ofLate Pleistocene extinction and still incomplete re-immigration of forest trees and suggest that the discontinuous distribution of Nothofagus is mainly the result of climate and competition (McGlone 1985;Sweetapple 1985;Wilson 1987). J.…”
Section: Introductionmentioning
confidence: 99%